IMPLANTATION AND RESTORATION OF TEETH: ERRORS AND COMPLICATIONS AFTER IMPLANTATION - Nasiba Asrorovna, Xolboeva; Xidirnazar Beknazar Oʻgʻli, Buriev; Nurali Fazliddin Oʻgʻli, Bobojonov (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: This study is to evaluate the body’s response to temperature changes following dental implant surgery, specifically focusing on the natural increase in temperature post-surgery. Methods: Used involve observing patients after implant insertion, where a small incision is made in the gum to access the bone, and the implant is screwed into the jaw. This process disrupts bone tissue integrity, leading to a temporary rise in body temperature. Results: The results indicate that a temperature increase up to 38 degrees Celsius is normal within the first 2-3 days after surgery due to the body's natural response to microsurgical interventions in the oral cavity. Notably, implants are made from hypoallergenic materials, thus preventing allergic reactions. Novelty: Its exploration of the diverse patient responses to temperature changes, emphasizing that individual tolerance varies, with some patients feeling unwell even at 37 degrees Celsius. For managing elevated temperatures, the use of antipyretic drugs like Paracetamol or Ibuprofen is recommended. This research contributes to understanding postoperative reactions and patient care in dental implant procedures.